Financial Distress and Corporate Tax Avoidance: Does Profitability Matter? - Lady Karlinah; Hotma Glorya Ika Sari; Liem Yan Sugondo; Vivian Tanaya (Politeknik Ganesha Medan, 2026)
This study explores the association between financial crisis and business tax avoidance, utilizing profitability as a moderating variable and audit committee effectiveness as a governance device. There is conflicting evidence in previous research about whether financially troubled companies act aggressively when it comes to taxes. This study uses a random effect regression model to examine the suggested associations using panel data from 121 listed businesses throughout the 2022–2024 period. The effective tax rate measures corporate tax evasion, whereas financial distress indicators and return on assets measure financial distress and profitability. The data show that financial difficulty does not affect corporation tax evasion. However, profitability considerably moderates the link between financial distress and tax avoidance, showing that financially distressed firms with higher profitability are more likely to dodge taxes. Furthermore, tax evasion is significantly impacted negatively by audit committee effectiveness, underscoring the importance of internal governance in preventing opportunistic tax conduct. These data imply that business tax avoidance is driven by financial capacity and governance supervision rather than financial pressure alone.